Population structure of Geodorum densiflorum (Orchidaceae) in relation to habitat disturbance and vegetation characteristics - Siti - Nurfadilah (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Nurfadilah S. 2020. Population structure of Geodorum densiflorum (Orchidaceae) in relation to habitat disturbance and vegetation characteristics. Biodiversitas 21: 1422-1431. Habitat disturbance can have large impacts on the persistence, survival, and growth of plant populations, particularly for orchids, one of the most threatened plant families. The present study aimed to investigate the impact of habitat disturbance on the population of a terrestrial orchid, Geodorum densiflorum (Lam.) Schltr, in terms of its population structure which is important in determining population viability for the species survival. The species occurred in three habitat types (disturbed habitat i.e. totally converted habitat into cananga plantation, burnt habitat, and undisturbed habitat). Plots of 2 m x 2 m were established in these three habitat types and the population structure of G. densiflorum in these three habitat types was analyzed. After analysis, three population types could be distinguished (i) 'regressive population' in disturbed habitat characterized by the absence of seedlings and dominated by generative adults, (ii) 'dynamic population' in burnt habitat characterized by a large proportion of young individuals (seedlings and juveniles) relative to the adults, and (iii) 'normal population' in undisturbed habitat characterized by the prevalence of adults but a small proportion of young individuals. The variation in the population structure of G. densiflorum appears to be related to the difference in vegetation characteristics of the three habitat types. The absence of seedlings of G. densiflorum in disturbed habitat was related to the grasses dominating vegetation that could inhibit seedling recruitment of G. densiflorum. Grasses were absent and hardly occurred in burnt habitat and undisturbed habitat allowing seedling recruitments of G. densiflorum in these habitat types. The highest seedling proportion and density of G. densiflorum were observed in burnt habitat as burning can remove aboveground biomass and reduce competition with surrounding vegetation providing safe microsites for seedling establishment and recruitment. The present study has implication in the orchid conservation and provide recommendation for the orchid conservation (i) to avoid totally converted habitat as it had consequences on the absence of seedling recruitment (ii) to perform mowing and managed burning to increase seedling recruitment of G. densiflorum which is important for population enlargement, persistence, and survival.